2008
DOI: 10.1111/j.1540-8167.2007.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Contractility is Preserved After Successful Circumferential Pulmonary Vein Ablation in Patients with Atrial Fibrillation

Abstract: LAmax volume reduction following CPVA occurs regardless of the clinical efficacy of the procedure, whereas mean LAmin volume only decreased in patients without recurrences. LA EF was preserved or even increased in most patients with successful CPVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
2
32
1
1
Order By: Relevance
“…23- 25 In the present study atrial function recovery did not seem to be affected by the procedure efficacy (of eliminating the arrhythmia), possibly because of the lower rate of recurrence and the reduction of arrhythmic burden even in patients with AF recurrence.…”
Section: Baseline Laef and Laef Variation After Ablationmentioning
confidence: 71%
“…23- 25 In the present study atrial function recovery did not seem to be affected by the procedure efficacy (of eliminating the arrhythmia), possibly because of the lower rate of recurrence and the reduction of arrhythmic burden even in patients with AF recurrence.…”
Section: Baseline Laef and Laef Variation After Ablationmentioning
confidence: 71%
“…The challenge in predictive modeling stems from the limited overall understanding of the in vivo boundary conditions associated with the dynamic change in pressure and motion in the atria and atrial septum. Understanding of atrial septal motion has improved by the advent of newer imaging modalities such as three-dimensional echocardiography and cardiac MRI [28][29][30][31]. Further refinement of motion and force measurements will lead to improvements in the predictive capabilities of finite element analysis and the in vitro tests associated with cardiac device design.…”
Section: Discussionmentioning
confidence: 98%
“…These phenomena are thought to be due to the presence of atrial injury over an extensive area. Furthermore, Perea et al [42] reported that LAEF was preserved or increased in patients without arrhythmia recurrences after circumferential pulmonary vein ablation for AF but was decreased in those with arrhythmia recurrences. Thus, PAF patients with low LAEF may have extensive atrial damage due to atrial fibrosis, which may be a predisposing factor for the transition from PAF to CAF.…”
Section: Decrement Of Laefmentioning
confidence: 97%
“…Several studies have shown that PV isolation using radiofrequency ablation for AF can be effective in improving LA function [24,39,42,[67][68][69]. However, extensive RFCA and the MAZE procedure may potentially attenuate atrial mechanical function because of atrial scarring and loss of atrial myocardium caused by these techniques.…”
Section: Decrement Of Laefmentioning
confidence: 98%
See 1 more Smart Citation